The Effect of Credit Disbursement Effectiveness on Profitability: The Moderating Role of Non-Performing Loans in PNM’s Mekaar Program (2016–2024) - Putrihadiningrum, devika cherly; Violita, Cynthia Eka (Jurnal Ekonomi dan Kewirausahaan West Science, 2026)
The purpose of this study is to analyze the effect of credit disbursement on the profitability of PT Permodalan Nasional Madani (PNM) and to examine the role of Non-Performing Loan (NPL) as a moderating variable in the relationship between credit disbursement and profitability at PNM. This study employs an explanatory quantitative approach to analyze the impact of credit disbursement on profitability, with NPL serving as a moderating variable, focusing on the Mekaar Program of PT PNM for the period 2016–2024. The analysis was conducted using Moderated Regression Analysis (MRA) in EViews. The results indicate that credit disbursement has a negative and significant effect on the profitability of PT Permodalan Nasional Madani (PNM), and Non-Performing Loan (NPL) negatively and significantly moderates this relationship, meaning that the higher the NPL, the weaker the impact of credit disbursement on profitability.